History of HÜNKAR’S BATH, Degradation, Pollution and Decay of Harem Baths in Topkapi Palace: A Restoration Proposal for Baths of Harem at Topkapi Palace - Sedes, Fatma (CAP - Cadernos de Arte Pública / Public Art Journal, 2023)
It is known that the Sultan's bath was built by Mimar Sinan in the 15’th century and it is stated that it has preserved its originality until today. It is also known that the Valide Sultan bath was built in the 18’th century. The Valide Sultan bath was added next to the Hünkar’s bath. The bath rooms are rectangular in plan. Access to the Sultan's bath is provided from the Sultan's Sofa and the Sultan's bedroom via the bath corridor. The Hamam corridor, which is also connected to the corridor of the Valide Sultan suite, also provides easy access to the Valide Sultan Hamam. Harem baths are spacious places with their illuminated domes, height and interior decoration. The Sultan's bath consists of three sections, cold, warm and hot sections. There is a large rectangular planned area on the right side of the entrance, this area is the cold room of the bath. The cold section is illuminated with the help of bottle-shaped windows called ‘’elephant eyes’’ on its dome. To the left of the entrance door, there is a warm room, in this area there is a basin. At the entrance to the hot section of the bath, there is the area where the Sultan had his bath on the left, and this area is surrounded by gilded bronze metal motifs. There is a selsabil (fountain) right next to this area. There is a large basin opposite the entrance door of the warm area. And there is a selsabil (fountain) on the right side. There is also a basin on the right at the entrance of the hot area. There is a 19’th century ornaments in the bath. Classical period details were not found. The cubes that provide the acoustics of the Sultan's Bath are located in two spaces above the area where the Sultan's basin is located.